The Impact of Laser Irradiation Durations on Zinc Oxide Nanostructures' Crystallinity, Surface Morphology, and Electrical Properties in Palladium/Glass (مجلة العلوم الشاملة, 2025)
The LACBD technique is used to make ZnO nanostructures and thin layers of palladium (Pd) on glass. Crystallinity, surface morphology, and electrical characteristics were investigated at 20, 25, and 30 minutes of laser radiation. According to the XRD patterns, the generated ZnO-NSs are polycrystalline with a hexagonal/wurtzite structure and a preferential orientation along the c-axis, as observed on 002 planes. The thin surface was examined using a FE-SEM. The outcome indicates that the orientation and spatial growth of the nanostructure significantly depend on the presence of the Pd buffer layer. The findings showed that the polycrystalline ZnO-NSs' surface structures and topographical properties were significantly influenced by the duration of the laser irradiation. Keithley 2400 used to charactraze the photoelectric effects. Additionally, the efficiency of Pd/ZnO NSs/Pd in UV detection has been researched. Both in low light and UV radiation, the photodetector exhibits outstanding stability and reactivity.